(untitled) (Bangladesh Journal of Medical Physics, 2013)
Over the past years prosthetic legs have become much improved although complex. However their costs are high and are not within the reach of most people in the Third World. Low-cost fixed prostheses are available in the Third world countries of Asia and Africa, but these offer very basic movement with unnatural gait; climbing stairs gets quite difficult. The prosthesis being worked upon in the present work are for amputees with legs removed above the knee, and would offer a limited rotational movement of the knee joint under voluntary control of the wearer, driven by the EMG signals extracted from thigh muscles. The aim is to make it at a low cost, may be at a cost slightly higher than the passive ones, but allowing a better gait in walking, and in climbing stairs. An initial work was done in this direction by our extended group earlier; the present work gives further improvements. This involves redesigning of the motor and the gear system and that of the electronic circuitry for processing the EMG signals extracted from thigh muscles, interfacing the output to the microcontroller, rotating the motor in two directions thereby accomplishing the movement of the knee joint. The motor, geared down, is mounted horizontally and a pulley system drives the artificial knee joint. When complete, this will benefit a large number of handicapped people in the Third World. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14695 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 107-114